Effects of floodplain decoupling on taxonomic and functional diversity of terrestrial floodplain organisms - Franziska Wenskus; Christian Hecht; Daniel Hering; Kathrin Januschke; Georg Rieland; Andrea Rumm; Mathias Scholz; Arnd Weber; Peter Horchler (Ecological Indicators)
When rivers are dammed or incised, the adjacent floodplains are often hydrologically decoupled from the river, with potentially drastic impacts on terrestrial biotic communities. Morphological river restorations are not always successful in restoring biodiversity, but causes remain obscure. A better understanding of the association of river-floodplain connectivity and floodplain biota is therefore necessary. We compared diversity and composition of plant, mollusc, and carabid (ground beetle) communities from coupled and decoupled floodplain sections along the Elbe River to investigate how they are affected by floodplain decoupling. Our analyses include both taxonomic and functional diversity indicators based on traits that reflect how well-adapted species are to flood disturbance. We recorded a total of 202 plant species, 146 carabid species, and 41 mollusc species. Plants and molluscs showed lower species richness and lower shares of indicator species for periodically wet grassland in the decoupled sections, while these metrics were higher for carabids. Abundance of species adapted to high disturbance was lower for molluscs in the decoupled floodplain sections, indicating that communities in these sections are less adapted to near-natural disturbance regime, while this metric, again, was higher for carabids. Functional richness, i.e., the volume of multidimensional trait space occupied by a community, decreased in the decoupled floodplain section for all three organism groups. Our results underscore the complex responses of different organism groups to differences in river-floodplain connectivity and suggest that floodplain specialist species of less mobile groups are disproportionately negatively affected by floodplain decoupling, contrary to the flight-active carabids. To capture community dynamics and to ensure maximum efficiency of restoration and conservation activities, a variety of organisms and aspects of biodiversity (taxonomic and functional) needs to be considered.